PERSEPSI AKUNTAN PEMERINTAH TERHADAP PENGETAHUAN TEKNOLOGI INFORMASI YANG HARUS DIKUASAI OLEH AKUNTAN PEMERINTAH DI INSPEKTORAT DAERAH PROVINSI SULAWESI SELATAN - Albar, Nur Akhmad (Economics and Business Faculty UNUSIA, 2024)
NUR AKHMAD ALBAR. Assessing Accountants' Perceptions on the Importance of Information Technology at the Regional Inspectorate of South Sulawesi (supervised by Mahfud Nurnajamuddin and Asriady Bakri). This study rigorously aims to investigate and elucidate the perspectives about the information technology competencies required by government accountants. Descriptive qualitative research is employed in this study. Data collection technique was carried out through interviews with 3 informants working as accountants. The study's findings demonstrate that while all elements of information technology expertise are deemed relevant, government accountants are not required to possess all facets of IT expertise because the level of the skills needed varies based on the duties and position of each government accountant. The amount of expertise required by each accountant in each area of IT might differ depending on the complexity of the task, the demands of the work, and their own skill set.